EFEKTIVITAS PERLINDUNGAN HUKUM TERHADAP ANAK SEBAGAI KORBAN TINDAK PIDANA PELECEHAN SEKSUAL (Studi Putusan Nomor 24/Pid.B/2011/PN.Sri) - yandika pratama, Yuda; Jamba, Padrisan (SCIENTIA JOURNAL, 2023)
Cases of sexual violence against minors are a serious concern in the legal aspect of child protection.This research looks at the legal effectiveness of protecting children as victims of sexual abuse byusing violence. The case raised was decision Number 24/Pid.B/2011/PN.Sri which involved theDefendant Iskandar Wihyawari Alias Iskandar who was charged with violating Article 81 paragraph (1)of the Law of the Republic of Indonesia Number 23 of 2002 concerning Child Protection juncto Article64 paragraph (1) of the Criminal Code. Through the effectiveness of the law, the author explores theevents that occurred and their impact on the victim and the relevance of the law applied in thedecision. This research also highlights the importance of child protection and the joint responsibility ofthe government, society and legal institutions in preventing and taking action against sexual violenceagainst children